2009
DOI: 10.1111/j.1600-0560.2009.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome hybridization analysis of laser‐capture microdissected in situ melanoma

Abstract: In situ melanomas show characteristic chromosomal aberrations that are limited compared to melanomas that invade the dermis. Deletion of 13q found in in situ melanomas, which encompass the Rb1 tumor suppressor gene, might be one of the first events in the development of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…The reason for this difference may be that the majority cases in our study was in‐situ melanomas, while previous studies mainly included invasive lesions. And comparative genome hybridisation test has revealed that compared with invasive melanoma, in‐situ melanoma harbored relatively limited chromosomal aberrations 22 . Similar to the results of Romano et al 19 .…”
Section: Discussionsupporting
confidence: 80%
“…The reason for this difference may be that the majority cases in our study was in‐situ melanomas, while previous studies mainly included invasive lesions. And comparative genome hybridisation test has revealed that compared with invasive melanoma, in‐situ melanoma harbored relatively limited chromosomal aberrations 22 . Similar to the results of Romano et al 19 .…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, the relevance of RB1 to melanoma is not in question and this is highlighted by a recent CGH study that found that RB1 ‐loss is an early and defining change in melanoma (Vincek et al., 2009). However, our data shows that Rb1 ablation alone does not lead to a short‐term or long‐term loss of melanocyte homeostasis and apoptosis either in vivo or in vitro, irrespective of the developmental stage at which the recombination event driving deletion occurs.…”
Section: Resultsmentioning
confidence: 99%
“…BCL2L1 (also known as BCL-XL), located on chromosome 12q, was amplified in 40% of DM; it encodes the antiapoptotic protein Bcl-XL, which has been demonstrated to enhance CXCL8-induced angiogenesis in melanoma cells. 9 Also amplified was ARTN on chromosome 1p, which encodes the protein artemin, which is reported to promote invasion of pancreatic carcinoma, influence perineural invasion, and increase the oncogenicity and invasiveness of endometrial carcinoma. 10 Interestingly, the gene AMPK on chromosome 1p was also amplified; although adenosine monophosphate-activated protein kinase (AMPK) has proapoptotic properties, it is well known to be involved in UV-induced skin cell damage and also plays a major role in the regulation of vascular endothelial growth factor expression and has a potential role in tumor angiogenesis.…”
Section: Dna Copy Number Changesmentioning
confidence: 99%